The Translation of Euphemism in Political Discourse - Althawabeyeh, Mohannad Mohammad (2017)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Mohannad Mohammad Althawabeyeh entitled, "The Translation of Euphemism in Political Discourse," submitted in May 2017. Thesis advisor is Dr. Sattar Izwaini. Soft and hard copy available.